Loving our own bones : disability wisdom and the spiritual subversiveness of knowing ourselves whole - Belser, Julia Watts, 1978- (Beacon Press, 2023)
"A spiritual companion and political manifesto that cuts through objectification and inspiration alike to offer a powerful new account of disability in biblical narrative and contemporary culture"--